Micromorphology and formation mechanism of pisoliths in the Dehdasht bauxite deposits - Ali Reza Zarasvandi; Akram Foroughinia; Houshang Pourkaseb; Abbas Charchi; Somayeh Salamabellahi (Journal of Economic Geology, 2013)
The Dehdasht bauxite deposits are located 40 km northeast of Dehdasht in Kohgilouye and Boyer-Ahmad Province. It is a part of the Irano-Hymalayan karstic bauxite belt located in the upper part of karstic depressions of Santonian-Turonian Sarvak carbonate formation. The aim of this study is to determine various geneses of pisoliths and prevalent processes in bauxitization. For this purpose, laboratory experiments were carried out including qualitative mineralogical investigation by X-Ray Diffraction (XRD) and petrographic study of thin section. Bauxitization processes led to the formation of bohemite, diaspore, calcite, kaolinite, anatase, rutile, goethite, hematite and chlorite in these deposits. Bauxitization was developed by destruction of kaolinite and deferruginization and caused aluminium concentration in the deposits. Mineralogically, these deposits vary based on the presence of pyrite in the gray horizon in some deposits such as Mandan. Minerals were formed due to three stages of weathering, diagenetic and epigenetic processes. Based on quantitative mineralogical results of the bauxite horizons, depositional/diagenetic environments of the study area vary from vadose to phreatic. Micromorphological investigations show pisoliths with simple, vitreous, complex and oolithic cores and also discolored and broken pisoliths. Therefore, the deposits can be divided into three types: autochthonous, allochthonous and para-autochtonous. Dissolution features and kaolinization, deferruginization and diaspore formation in fractures demonstrate diagenetic and epigenetic processes that occurred after the formation of the deposits. Investigation of encrust particles frequency shows that particles with 50-200 micron in diameter, have the most frequency and simple fabric of ooliths shows short-term formation. Comparison of the frequency of encrust particles as well as TiO2/Al2O3 variation diagrams, indicates that some deposits such as Mandan had lengthier bauxitization time.